Distinguishing fuel and lubricating oil combustion products in diesel engine exhaust particles. Issue 5 (4th May 2019) - Carbone, Samara; Timonen, Hilkka J.; Rostedt, Antti; Happonen, Matti; Rönkkö, Topi; Keskinen, Jorma; Ristimaki, Jyrki; Korpi, Heikki; Artaxo, Paulo; Canagaratna, Manjula; Worsnop, Douglas; Canonaco, Francesco; et al.
Abstract: The main sources of particulate emissions from engines are fuel and lubricating oil. In this study, particles emitted by a medium speed diesel engine for locomotive use were characterized chemically by using a soot particle aerosol mass spectrometer (SP-AMS). Additionally, positive matrix factorization (PMF) was applied to the SP-AMS data for the separation of fuel from lubricating oil and/or oil additives in diesel engine emissions. The mass spectra of refractory species, i.e., metals and rBC, were included in the PMF input matrix in addition to organics in order to utilize the benefit of the SP-AMS to measure non-refractory and refractory species. In general, particulate matter emitted by the diesel engine was dominated by organics (51%) followed by refractory black carbon (rBC; 48%), trace metals and inorganic species (1%). Regarding the sources of particles, PMF indicated four factors for particle mass of which two were related to lubricating oil-like aerosol (LOA1, 29% and LOA2, 24%) and two others to diesel-like fuel aerosol (DFA1, 35% and DFA2, 12%). The main difference between LOA1 and LOA2 was the presence of soot in LOA1 and metals in LOA2 factors. DFA factors represented burned (DFA1) and unburned fuel (DFA2). The results from the PMF analysis were completed with particle size distributions, volatility measurements and particle morphology analyses. Copyright © 2019 American Association for Aerosol Research